The homotopy simulation of MHD time dependent three dimensional shear thinning fluid flow over a stretching plate. (April 2022) - Khan, Kashif Ali; Seadawy, Aly R.; Raza, Nauman
Abstract: This article is devoted to investigate the analytic-numeric solutions of an unsteady 3-D MHD shear thinning fluid flow which is embedded in a permeable medium through a stretching sheet along with the attributes of heat transfer. The similarity transformation is adopted to convert the PDEs of current model into its dimensionless form. Then the model is solved by using an algorithm of a robusting technique named as method of Homotopy analysis (HAM). After that, solutions are compared by invoking Runge-Kutta based shooting method. All the symbolic calculations and vived construction of profiles are done by MATHEMATICA and MATLAB. To further discuss the HAM's convergence and the results homology of the flow model; tabularization is used against multitudinous parameters.